Changes in sex difference in swimming speed in finalists at FINA World Championships and the Olympic Games from 1992 to 2013 - Wild, S.; Rüst, C.; Rosemann, T.; Knechtle, B. (BMC Sports Science, Medicine and Rehabilitation, 2014)
This study investigated swimming speeds and sex differences of finalists competing at the Olympic Games (i.e. 624 female and 672 male athletes) and FINA World Championships (i.e. 990 women and 1008 men) between 1992 and 2013.